The THE CONCEPT OF JUSTICE IN THE PERSPECTIVE OF ISLAM AND PANCASILA - Manggala, Kayan; Badruddin (CV. Fahr Publishing, 2024)
Justice is a fundamental value recognised in various ethical and legal systems, including in Islam and Pancasila. The objectives of this study are (1) to find out the meaning of justice. (2) to know the concept of justice in Islamic Perspective. (3) to find out the concept of Justice in the Perspective of Pancasila. The method used to explore this is a literature study with qualitative descriptive analysis. The results of this study are three, namely (1) the meaning of justice from various languages including: Justice (English), al-adl' (Arabic), and Adil (Indonesian) (2) The concept of justice from an Islamic perspective is the concept of justice that comes from the Qur'an as the main foundation, this concept establishes haq and batil by verifying it through identification (taaruf), research (tabayyun), proof (shahadah), analysis and synthesis (dhikr) of Allah's verses that are plastered in every direction (including in humans and social reality), as well as the Qur'an, so that it is not mistaken in drawing conclusions. (3) justice in the perspective of Pancasila is justice that is the source of the framework of the five precepts in Pancasila, including: Deity, Humanity, National Unity, Consensus, and Social Justice.